Mental and social well-being versus physical disability – the diagnosis of the problems - Rzempowska, Jadwiga; Zysnarska, Monika; Stawińska-Witoszyńska, Barbara; Kłos, Jan; Gromadecka-Sutkiewicz, Małgorzata; Krzyżaniak, Alicja; Maksymiuk, Tomasz (Journal of Medical Science, 2016)
Introduction. Health is most frequently defined as full well-being in the biological, psychological and social sense. A disorder of a person’s functioning in any of these spheres triggers changes in the remaining ones. Such destabilization may result in losing the ability to cope with everyday situations.Aim. The objective of the study was to recognize the self-assessment of the mental well-being, along with the selected elements of the social situation, of young, physically impaired persons living in the countryside.Material and methods. The research was conducted on the population of physically disabled individuals – with legally granted disability class, living in the countryside in the Wielkopolskie province, aged 18–45 years. The applied technique was an interview based on an original questionnaire with 96 questions.Results. Over a half of the respondents confirmed that their disability affects their mental state. They often suffer from depressed mood, feeling of loneliness, feeling of being a “burden” for others. As many as 41.7% of respondents admitted suicidal thoughts.Conclusions. The situation of disabled people living in the countryside is particularly difficult. Financial problems, unemployment, limited access to health care negatively influence the mental well-being of young persons, often leading to a depressed mood. In consequence, they often experience suicidal thoughts.